Pediatric pancreatic acinar cell carcinoma with a non-canonical BRAF-KMT2C fusion and a classic SND1-BRAF fusion: a case report and literature review - Yaqin Wang; Jiasi Zhang; Dimin Nie; Ai Zhang; Qun Hu; Aiguo Liu (BMC Pediatrics)
Abstract Background Pediatric pancreatic acinar cell carcinoma (PACC) is an exceptionally rare and poorly understood malignancy with a challenging prognosis. Its clinical presentation is often atypical, and standardized treatment guidelines are currently unavailable. While genetic alterations in adult PACC have been studied to some extent, knowledge of genetic abnormalities in pediatric cases remains limited. Case presentation We report a case of pediatric PACC in a 7-year-old male presenting with a large, non-tender abdominal mass (11 cm x 11 cm) on the right side. Pathological and imaging evidence confirmed the diagnosis of PACC, with no lymph node infiltration or distant metastasis. Comprehensive genomic profiling by next-generation sequencing identified a non-canonical BRAF fusion with KMT2C at the DNA level and a classic SND1-BRAF fusion at the RNA level. The patient underwent surgical resection through a Whipple operation followed by six cycles of mFOLIRINOX chemotherapy and radiation therapy, achieving a favorable outcome up to now. Conclusions Next-generation sequencing has demonstrated significant value in identifying genetic fusions in pediatric PACC. In our case report, we identified both the classical SND1-BRAF fusion, commonly associated with PACC, and a previously unreported nonclassical BRAF-KMT2C fusion. These findings underscore the critical role of BRAF alterations as key drivers of oncogenesis in PACC. A multidisciplinary treatment strategy integrating surgery, chemotherapy, and radiation therapy offers a promising precedent for improving therapeutic outcomes and prolonging survival in pediatric PACC cases.